2009
DOI: 10.1093/ndt/gfp235
|View full text |Cite
|
Sign up to set email alerts
|

Value of the RIFLE classification for acute kidney injury in diffuse proliferative lupus nephritis

Abstract: The RIFLE classification is predictive of progression and short-term prognosis of AKI in diffuse proliferative lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…10,11 Successive increases in severity of RIFLE category were associated with higher mortality in critically ill patients and the RIFLE classification was useful for predicting full recovery of renal function. [12][13][14][15][16][17] In this study, there was no significant difference of recovery rate and the mean time to recovery among AKI-R, AKI-I, and AKI-F groups, although there was a tendency that it took longer time to recovery in more severe AKI patients. Further analysis showed that renal function recovery was affected mainly by immunosuppressive therapies.…”
Section: Discussionmentioning
confidence: 82%
“…10,11 Successive increases in severity of RIFLE category were associated with higher mortality in critically ill patients and the RIFLE classification was useful for predicting full recovery of renal function. [12][13][14][15][16][17] In this study, there was no significant difference of recovery rate and the mean time to recovery among AKI-R, AKI-I, and AKI-F groups, although there was a tendency that it took longer time to recovery in more severe AKI patients. Further analysis showed that renal function recovery was affected mainly by immunosuppressive therapies.…”
Section: Discussionmentioning
confidence: 82%
“…In lupus nephritis, a considerable proportion of patients present with AKI. 15 However, currently, there is a lack of detailed description of lupus nephritis patients complicated with AKI, including clinicopathological features and renal outcome of long-term follow up, especially after the new ISN/ RPS classification of lupus nephritis was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…44, 45 The incidence of progressive to chronic kidney disease was proportional to AKI severity by RIFLE classification. 46, 47 In addition, AKI will directly contribute to distant organ dysfunction through the mechanism of oxidative stress, immunity and inflammation. 15,48-50 This means AKI severity by RIFLE classification represents not only kidney damage but also imbalance between the kidney and other organ systems.…”
Section: Hsieh Mj Et Almentioning
confidence: 99%